2007
DOI: 10.1007/s00421-007-0574-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise mode on heart rate variability during steady state exercise

Abstract: This study examined the effect of exercise mode on geometrical, and time and frequency domain measures of heart rate variability (HRV) during steady-state, moderate intensity exercise of the same HR. Seventeen healthy, active male participants volunteered for this study and completed a treadmill VO2max determination. One week later, cardiorespiratory, perceptual and HRV measures were recorded during seated rest (15 min) and consecutive bouts (15 min) of steady-state exercise at 50 and 65% of maximal HR. Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 43 publications
(79 reference statements)
9
60
2
3
Order By: Relevance
“…In addition to the significant differences of absolute spectral powers the increase of SDNN also demonstrates the distinct autonomic HR modulation under the different contraction modes. Together, these results speak for an increased dual autonomic cardiac modulation under ISO and supports evidence from recent studies [7,24,67]. Complementary to traditional HRV measures, entropy was significantly decreased during ISO, pointing towards an enhanced regularity of the heart beat series [37,[40][41][42].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to the significant differences of absolute spectral powers the increase of SDNN also demonstrates the distinct autonomic HR modulation under the different contraction modes. Together, these results speak for an increased dual autonomic cardiac modulation under ISO and supports evidence from recent studies [7,24,67]. Complementary to traditional HRV measures, entropy was significantly decreased during ISO, pointing towards an enhanced regularity of the heart beat series [37,[40][41][42].…”
Section: Discussionsupporting
confidence: 86%
“…Leicht and his associates compared the cardiovascular response to dynamic muscular activity of different muscle groups at 50% maximum HR (HRmax) and 65% HRmax, respectively. They have found greater HRV despite lower oxygen consumption during upper body dynamic exercise compared to lower or whole body dynamic exercise at similar HR and concluded that greater HRV may represent increased vagal or dual autonomic modulation [24]. Cottin et al compared HRV indices during a judo randori vs. ergometer cycling eliciting the same HR level [25].…”
Section: Introductionmentioning
confidence: 99%
“…The exercise-evoked HRV changes could potentially provide disease-related information [11] but may easily be overlooked by single laboratory assessments that usually do not last long. A couple of previous studies have examined acute HRV changes induced by different activity patterns, e.g., intense exercise or low-intensity exercise, isometric or dynamic exercise [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Een so 'n tegniek is die berekening van harttempo-variasie (HTV) wat die meting van die variasie in die lengte van die RR-interval behels (die tyd wat verloop tussen opeenvolgende hartkontraksies) (Chen et al 2010;Pagani et al 1986; Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology 1996; Lewis et al 2007;Leicht, Sinclair & Spinks 2008). Hierdie tegniek verskaf ook inligting oor die werking van die outonome senustelsel (OSS) (Chen et al 2010;Leicht et al 2008;Lewis et al 2007).…”
Section: Inleidingunclassified
“…Hierdie tegniek verskaf ook inligting oor die werking van die outonome senustelsel (OSS) (Chen et al 2010;Leicht et al 2008;Lewis et al 2007). …”
Section: Inleidingunclassified